Tangible effects of the COVID-19 pandemic: A fall in dexterity amongst surgical trainees?. Issue 2 (May 2022) - Gowda, Siri; Swamy, Gokul Kanda; Veerattepillay, Rajan; Rajasundaram, Ramanan; Hanchanale, Vishwanath; Gowda, Basavaraj; Wilkinson, Beverley; Biyani, Chandra Shekhar
Background: The coronavirus pandemic has had an indisputable impact on surgical training. The qualitative effect on the perceived confidence and capability of trainees has been widely reported. In order to fully delineate the scope of the problem, quantitative data is also required. Methods: This cross-sectional study collected compared data on the laparoscopic skills (pre- and post-pandemic) of first-year urology residents in the United Kingdom, who attended the annual Urology Simulation Boot Camp (USBC) in 2018 and 2019 (pre-pandemic), and 2021 (post-pandemic). Results: Pre-pandemic group performance was significantly better in 2 out of 4 tasks (Task 3 p < 0.001) (Task 4 p = 0.003) during the practice session. During the assessment, pre-pandemic group performance was better (p = 0.017) for Task 2 and significantly faster (p = 003) for Task 4. Conclusions: Our results provide evidence to support the notion that the coronavirus pandemic has had a tangible and detrimental effect on the technical skills of surgical trainees.